A survey on the milk chemical and microbiological quality in dairy donkey farms located in NorthWestern Italy. (April 2015) - Cavallarin, Laura; Giribaldi, Marzia; Soto-Del Rio, Maria de los Dolores; Valle, Emanuela; Barbarino, Gandolfo; Gennero, Maria Silvia; Civera, Tiziana
Abstract: There is a growing interest in donkey's milk as food for sensitive consumers, such as infants with cow's milk protein allergy and elderly people. The aim of this study was to carry out a survey on the dairy donkeys farming in Piedmont, Italy. The research was conducted in order to analyze the farm characteristics as well as the chemical and microbiological quality of milk. All the farms were small-sized, family-run, and, in most cases, animals were farmed semi-extensively. The donkey milk from Piedmont farms was characterized by a protein content around 1.5 g/100 mL and a fat content lower than 0.1 g/100 mL. Lysozyme activity was considerably higher than that reported in raw cow milk. The milk microbiological profile greatly differed among the farms. Milk sampled in the farm that performed hand milking showed total viable counts significantly lower than milk collected in the farms equipped with automatic milking. Samples were tested for several pathogens and negative results were observed, except for the detection of Bacillus cereus in one sample. The survey provided useful data for the laying down of recent regional regulation for the production and commercialization of donkey's milk. The results of the survey indicate that further research is needed in order to define the best management and nutritional strategies for the improvement of the quali-quantitative production of dairy donkeys. Highlights: A survey of the donkey milk (DM) farms in Piedmont, Italy, was performed. DM presented a mean protein content of 1.5% and mean fat content lower than 0.1%. Microbiological profiles differed among farms and milking practices. Bacillus cereus was detected in one of the farms. Data were used for laying down of regional regulation of DM production.